L’établissement fortifié de hauteur alto-médiéval de Château-sur-Salins (Salins-les-Bains, Jura) - Philippe Gandel; David Billoin (Gallia)
The hilltop fortified settlement of Château-Salins is established on a vast plateau overlooking a major circulation axe, near a town whose dynamism along the Early Middle Ages is related to salt exploitation. The civilian, religious and defensive substructures, installed ex nihilo on two areas of the plateau since the early 7th c. AD, must correspond – considering their ostentatious features – to a vast project initiated by a strong civilan or religious power.